The oxidized phospholipid oxPAPC protects from septic shock by targeting the non-canonical inflammasome in macrophages - Lan H. Chu (Nature Portfolio, 2018)
Non-canonical inflammasome activation is mediated by caspase-11 in mice and caspase-4 in humans. Here the authors show that oxidized 1-palmitoyl-2-arachidonoyl-sn-glycero-3-phosphorylcholine (oxPAPC) competes with LPS for binding to these caspases and in so doing is a negative regulator of non-canonical inflammasome activation in macrophages, but not in dendritic cells.